Desenvolvimentismo e pragmatismo: o ideário do MEC nos anos 1950 Developmentism and pragmatism: the ideas pursued by the Brazilian ministry of education in the 1950's - Miriam Waidenfeld Chaves (Cadernos de Pesquisa, 2006)
Este artigo tem como objetivo mostrar como o desenvolvimentismo e o pragmatismo, dois pensamentos de natureza distinta, contribuem, cada um à sua maneira, para fundamentar uma política de reconstrução nacional nos anos 1950, em particular no âmbito do Ministério da Educação e Cultura - MEC. A idéia central é que, por circularem nos mesmos espaços institucionais, esses dois pensamentos acabam por interagir um com o outro, de tal modo que a ideologia desenvolvimentista se transforma em um solo fértil para a retomada e expansão do pragmatismo. Para explicar esse fenômeno, recorda-se que ambos se ancoram em uma concepção de cunho prático baseada na política. Chama-se a atenção para a maneira como o Instituto Superior de Estudos Brasileiros - Iseb - e o Instituto Nacional de Estudos Pedagógicos - Inep -, dois órgãos do MEC responsáveis por fomentar um pensamento nacional, se apropriam desses ideários para a formulação e a implementação de políticas de reconstrução nacional. This paper aims to discuss how two distinct definitional concepts - developmentism and pragmatism - contributed, in their own particular ways, to the underlying foundations upon which a national reconstruction policy was implemented in the 1950's. Special consideration shall be given to the fact that their unruffled co-existence within the very same institution - the Brazilian Ministry of Education (MEC) - turned the developmentist ideology into a fertile ground for the rebirth and growth of pragmatism. Upon such consideration, this paper shall highlight (1) the fact that both concepts are based upon an eminently practical political mindset and (2) the means employed by ISEB (Higher Institute of Brazilian Studies) and INEP (National Institute of Pedagogical Studies) to develop and implement national reconstruction policies. These institutions were institutions within MEC whose think-tank board members aimed at scaffolding the national frame of thinking.